MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL LOMPAT TALI PADA USIA 5-6 TAHUN DI PAUD TUNAS MEKAR PLUS TAHUN PELAJARAN 2017/2018 - Suhartini - Suhartini; Jarwoko - Jarwoko (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
The researcher conducted a classroom action research to improve students gross motor skill, especially for the physical motor skill such as strength and balance through traditional game jumping rope. This study was conducted in group B at Tunas MekarPlus Playgroup and involved thirteen students as the research subjects. Moreover, two cycles were applied in this study with three meeting in each cycle. To collect the data, observation and documentation were employed. In addition, the data was analyzed through mean score analysis by determining the progress of students’ gross motor skill in each cycle which then displayed in table for better understanding. Having analyzed the data, students’ average score in cycle 1 was 47% and then increased into 80% in cycle 2. It shows that students’ gross motor skill has developed as expected, i.e.: ability to jump. Regarding to the strength, students have reached the targeted standard, i.e.; 60%-79%, classified in ‘develop as expected’.